Administrative Reconfiguration in Nangarhar Province under Taliban Rule Post-2021 (Al-Qamar, 2025)
This paper examines the administrative changes in Nangarhar Province after the Taliban's resurgence in Afghanistan in August 2021. This paper employs a qualitative research methodology, incorporating interviews with local officials, administrators, scholars, and journalists, to examine how the Taliban reformed provincial administrative systems, dismantled existing governance structures, and established new institutional frameworks consistent with their ideological model. Research reveals that essential state agencies, including the Human Rights Department, Public Affairs Department, and Ministry of Women’s Affairs, were dismantled and supplanted by entities such as the Amr Bil Maruf wa Nahi Anil Munkar Department and district assistance centers. The Taliban implemented consolidated appointment procedures, restructured
Keywords: Taliban; Nangarhar; administrative transformation; governanc; Afghanistan; institutional restructuring